KEBERADAAN PERKEBUNAN SAWIT DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT MELALUI KEMITRAAN - Devrayno (Jurnal Ilmu Hukum Tambun Bungai, 2018)
The oil palm plantation industry has an important an trategic role in national development, one of the form of plantation business in improving the welfare of the community, especially the coommunity of planter around the planters by way of partnership. This partnership relation must be set forth in the agreement so stricly regulate the rights and obligations of parties both the pantation companies and the planters themselves. The partnership has a meaning to bring planters have moral responsibility to develop the plantation community to the able their plantation so that it can improve their welfare.